ANALISIS PERLINDUNGAN HUKUM BAGI FRANCHISEE AKIBAT FRANCHISOR YANG MELAKUKAN PEMUTUSAN PERJANJIAN FRANCHISE SECARA SEPIHAK - Monica Wijaya; Urbanisasi (LPPM, Universitas Muhammadiyah Riau, 2023)
In the franchisee agreement there is still an imbalance of position between the franchisor and the franchisee. This is because the clauses in the franchisee agreement are made unilaterally by the franchisor without negotiation, while the franchisee can only accept. In addition, there are also problems regarding the unilateral termination of the franchisee agreement by the franchisor which is very detrimental to the franchisee. The purpose of this research is to find out whether the unilateral termination of the agreement by the franchisor is permitted in Government Regulation Number 42 of 2007 concerning Franchising, Minister of Trade Regulation Number 71 of 2019 concerning the Implementation of Franchising and the Civil Code. Then it also aims so that we can find out about legal protection for franchisees who experience these problems. The research method used in this article is a normative legal research method. Meanwhile, the approach used is the statutory approach and the conceptual approach. Based on the results of the research that has been done, it can be concluded that unilateral termination of the agreement by the franchisor is not allowed, then the franchisee who has suffered losses due to this problem can claim compensation from the franchisor.